Antimony and arsenic contamination in water from antimonite mineralization: a case study from Turhal (Tokat, Northern Turkey). Issue 3 (14th July 2022) - Kurt, M. A.; Yıldırım, Ü.; Güler, C.; Güven, O.
Abstract: The sources and fate of antimony (Sb) and arsenic (As) in water resources around antimonite (a.k.a. stibnite) deposits is of great concern due to their adverse effects on the environment and human health. The aim of this study was to determine geochemical compositions of gangue/ore material and water samples collected in and around the antimonite deposits located near Turhal (Tokat, Northern Turkey). Turhal antimonite deposits, recognized as the largest in Turkey, are hosted in pre-Upper Jurassic low-grade metamorphic rocks where the antimonite ore is mainly composed of stibnite and quartz. Quartz is also the dominant gangue mineral, with minor amounts of carbonates. The ore samples contain high concentrations of Sb (27.98 − 60.83 wt.% as Sb2 O3 ) and As (3453 − 5010 ppm). The gangue material contains significant amounts of As (529 ppm), Cr (664 ppm), and Ti (256 ppm). Water samples collected from the study area are characterized by slightly alkaline pH (6.48–8.40) and low Eh (–46 to –5 mV) with electrical conductivity values ranging between 571 and 1607 µS cm −1 . There is a significant trace element contamination in the aquifer system, especially in water samples collected from the areas hydrologically downgradient of antimonite deposits, where concentrations (in µg L −1 ) reach up to 271.6 for Sb, 429.4 for As, and 2203 for B. There is a high risk of toxicity for the livestock, as well as the human population consuming their products, since Sb and As contaminated springs in the region are used for watering farm animals.